Morphological characterization of cinnamon bark and powder available in the Serbian market - Jeremić, Katarina; Kladar, Nebojša; Vučinić, Nataša; Todorović, Nemanja; Hitl, Maja; Lalić-Popović, Mladena; Gavarić, Neda (Biologia Serbica, 2019)
In vitro and in vivo research suggests that cinnamon, which is widely used as a spice, could have significant medicinal potential. However, the problem of using this spice for medicinal purposes is that there are hundreds of species and subspecies of cinnamon plant, and although the official source for spice production is Cinnamomum verum (zeylanicum) – Ceylon cinnamon; C. cassia – Chinese cinnamon, and C. burmanii – Indonesian cinnamon are commonly found on the market. In powder form it is practically impossible to distinguish between these types of cinnamon without a microscope or analytical methods. The aim of the present study is the analysis of cinnamon on the Serbian market, including verification of its origin using macroscopic and microscopic methods. Bark samples were observed under a binocular magnifier ZEISS STEMI 508 with AXIOCAM ERc 5s camera to determine fine differences between species. The powder was examined under an AXIOLAB A.1 binocular microscope with AXIOCAM ERc 5s camera. During macroscopic identification, visual differences were clearly detected and results clearly showed that in toto bark of these three species of cinnamon can be differentiated even if the type and origin are not designated on the package. During microscopic observation of powdered samples, Cinnamomum burmanii was the easiest for differentiation because of the existence of authentic plates of calcium oxalate. However, more specific characters are needed in order to distinguish between Ceylon and Chinese cinnamon powder samples. One of the possible ways to overcome this problem may be through the measurement of fiber diameters where significant differences were found. Based on the obtained results it can be concluded that microscopic techniques, which are affordable, may be a useful tool for elucidation of the differences between the most commonly present cinnamon species on the market.